Interaction of Mathematics Learning in Inclusive School - Rahmadini, Widya; Fatimah, Siti (Universitas Teknokrat Indonesia, 2025)
Interaction becomes a very important thing in mathematics learning activities because it can help students gain good conceptual understanding, including in inclusive schools that involve regular students and students with special needs in the same scope. This study aims to describe the interaction in mathematics learning in grade VII at one of the inclusive middle schools in Bandar Lampung, Lampung Province. The subjects in this study were 23 regular students, 2 slow learners, and 1 autistic student. This study used a qualitative approach with a case study method on teacher-student interaction in mathematics learning. The research instruments used were observation sheets, Flanders Interaction Analysis Category System (FIACS) matrix, and unstructured interviews. Furthermore, data analysis was carried out through three stages, namely data reduction, data presentation, and conclusion drawing. The results showed that the dominance of teacher talk proportion was in the aspect of encouraging with an average of 34.31% and the aspect of closed response in student talk to the teacher amounted to 70.65% which appeared during the core learning activities in understanding mathematical concepts and problems, while discussions conducted by students with special needs dominated the aspect of discussion during learning activities involving peer tutors, which was 21.88%. This means that mathematics learning in this study forms student activities in following procedural instructions from the teacher, students and teachers communicating mathematics, and jointly constructing mathematical truths. The interaction that occurs in mathematics learning forms a multi-directional pattern involving reciprocal interactions between teachers, regular students, and students with special needs.